2022
DOI: 10.1101/2022.10.24.513474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposons repressed by H3K27me3 were co-opted as cis-regulatory elements of H3K27me3 controlled protein coding genes during evolution of plants

Abstract: The mobility of transposable elements (TEs) contributes to evolution of genomes. Meanwhile, their uncontrolled activity causes genomic instability and therefore expression of TEs is silenced by host genomes. TEs are marked with DNA and H3K9 methylation that are associated with silencing in flowering plants, animals, and fungi. Yet, in distantly related eukaryotes TEs are instead marked by H3K27me3 deposited by the Polycomb Repressive Complex 2 (PRC2), an epigenetic mark associated with gene silencing in multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 82 publications
1
8
0
1
Order By: Relevance
“…Considering the observed H3K27me3 enrichment at a few TE-related genes in 2h1 plants, we extended our analysis to TEs, which typically lack H3K27me3 in Arabidopsis 49,50 . This revealed that 1066 TEs are newly marked by H3K27me3 in 2h1 plants, most frequently over their entire length, thereby excluding a priori the possibility that H3K27me3 TE enrichment is due to spreading from neighboring genes (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the observed H3K27me3 enrichment at a few TE-related genes in 2h1 plants, we extended our analysis to TEs, which typically lack H3K27me3 in Arabidopsis 49,50 . This revealed that 1066 TEs are newly marked by H3K27me3 in 2h1 plants, most frequently over their entire length, thereby excluding a priori the possibility that H3K27me3 TE enrichment is due to spreading from neighboring genes (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Since KNOX/ BELL are conserved targets of PRC2, and it was shown that knockout of MpE(z)1 results in lethality at the haploid stage, while knockout of MpE(z)2/3 impedes sporophyte development, it is possible that MpKNOX is silenced by H3K27me3 in egg cells (Flores-Sandoval et al, 2016;Montgomery et al, 2022). This hypothesis is supported by the finding that KNOX and BELL loci are covered by H3K27me3 in vegetative tissues of the Marchantia gametophytes (Hisanaga et al, 2022). These findings indicate that PRC2 regulates haploid-to-diploid transitions in land plants with gametophyte-dominant life forms (Figure 1).…”
Section: Control Of Cell Identity and Haploid-to-diploid Transitionmentioning
confidence: 88%
“…It was shown that around half of all TEs are targets of H3K27me3, while in Arabidopsis only 4% of TEs carry H3K27me3 (Johnson et al, 2004;Lafos et al, 2011;Mikulski et al, 2017;Oh et al, 2008). Moreover, knock-out of the one E(z) homolog that is present in the alga's genome resulted in complete loss of H3K27me3 which correlated with an induction of a large fraction of normally repressed TEs, suggesting that PRC2-mediated H3K27me3 deposition is an important TE silencing mechanism in this unicellular organism (Hisanaga et al, 2022). It is worth mentioning that while 25% of the Arabidopsis genome is comprised of TEs, only 0.7% of the Cy.…”
Section: Maintenance Of Genome Dosage and Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…What was the original function of the Polycomb system? There is accumulating evidence that the primary purpose of PRC2 in unicellular eukaryotes is the silencing of transposable elements to protect genome integrity (Shaver et al 2010;Xu et al 2021;Montgomery et al 2020;Hisanaga et al 2022). Similarly, in addition to gene control, plant PcG proteins ensure transcriptional repression of repetitive genomic elements and transposable elements (Fuchs et al 2008;Montgomery et al 2020;Shaver et al 2010;Widiez et al 2014;Deleris et al 2012;Moreno-Romero et al 2016;Schubert 2019).…”
Section: Discussionmentioning
confidence: 99%